RESPONS MAHASISWA TERHADAP WEBSITE PURNAMA JAYA FARM SLEMAN - Ghani Pradita; Sunarru Samsi Hariadi; Harsoyo Harsoyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This study aims to identify creation of Purnama Jaya Farm :s website, knowing the response of students toward the website, and the influencingfactors of it. The method used in this research was descriptive approach by survey technique. The sampling of department were done purposively, while the sampling of students was done randomly. The number of total sample was 64 students from Department of Agricultural Socio-Economics from class of 2010 to class of20 13. From each class taken 8 Agribusiness students and 8 Agricultural Extension and Communication students. The analysis methods used proportion test and multiple linier regression analysis. The result of this research showed that response of students toward Purnama Jaya Farm :s website were high. The quality of information and ease of use positively affected toward response of students, while sex, academic program, degree of education, perception, quality of system, and playfulness didn't have significant affect